Eliminate the parameter. x = t2 + 1, y = t2 – 1

Eliminate the parameter. x = t2 + 1, y = t2 – 1

x – y = 2 Step-by-step explanation: The given equations are x = t² + 1 and y = t² – 1 We have to eliminate the parameter t from these equations. Since x = t² + 1 t² = x – 1 and y = t² + 1 t² = y – 1 Now we equate both the equations x – 1 = y – 1 x – y = 1 + 1 x – y = 2 Therefore, answer is x – y = 2

understand that i don’t know the answers will someone answer his question

step-by-step explanation: i believe its “c” because all of the other options include a but it could be d because there is a way of financing with cash at certain places but its uncommon.

Also Read :   What did the athlete order when he needed a huge of mashed potatoes?

Leave a Comment